2020
DOI: 10.1111/1744-7917.12869
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of specific cuticular proteins analogous to peritrophin 3 genes disrupt larval and ovarian development in Bactrocera dorsalis (Diptera: Tephritidae)

Abstract: Cuticular proteins (CPs) are critical components of the insect cuticle and play important roles in maintaining normal insect development and defense against various environmental stresses. The oriental fruit fly (Bactrocera dorsalis) is one of the most destructive pests worldwide, and its eight CPs analogous to peritrophin 3 (BdCPAP3) family genes have been identified in our previous study. In the present study, we further explored the possible roles of CPAP3 genes in B. dorsalis development. Each sequence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…To confirm the consistency and specificity of all generated products, melting curve analysis was conducted to check all reactions from 60 to 95°C at the end of each RT–qPCR. Previous evaluations 39,40 showed that a‐tubulin (GenBank accession number: GU269902) had excellent stability for spatial and temporal distribution in B. dorsalis , and so was used as an internal reference gene. Relative expression levels of BdDDC were determined using the 2 −ΔΔCT method, 41 and the RT–qPCR primers are given in Table S4.…”
Section: Materials Andmethodsmentioning
confidence: 99%
“…To confirm the consistency and specificity of all generated products, melting curve analysis was conducted to check all reactions from 60 to 95°C at the end of each RT–qPCR. Previous evaluations 39,40 showed that a‐tubulin (GenBank accession number: GU269902) had excellent stability for spatial and temporal distribution in B. dorsalis , and so was used as an internal reference gene. Relative expression levels of BdDDC were determined using the 2 −ΔΔCT method, 41 and the RT–qPCR primers are given in Table S4.…”
Section: Materials Andmethodsmentioning
confidence: 99%
“…In Eriocheir sinensis , chitinases involved in chitin binding showed a high expression level during the postmolt and ecdysis stages, and a very low level at the intermolt and premolt stages were detected ( 34 ), which indicated a potential role of chitin binding to molting. Meanwhile, researchers found that cuticular proteins analogous to peritrophins were abundantly distributed in the cuticle ( 35 37 ), and the knockdown of the genes can cause a delay of pupariation or mortality ( 38 , 39 ). The relationship between ETH and peritrophins in S. paramamosain still needs more research.…”
Section: Discussionmentioning
confidence: 99%
“…In studies on Tribolium castaneum, silencing of genes TcCPR27 and TcCPR18 resulted in shortened elytra in adults, accompanied by wrinkling, bending, and porous structures, and death approximately one week after eclosion [20]. In Bactrocera dorsalis, injection of dsRNA targeting four cap3 genes significantly delayed larval-to-pupal development, with pupation time significantly longer than the control injection [21]. In Locusta migratoria, the absence of LmCP8 affected the structural development of the ovipositor, resulting in a large number of unproduced egg capsules being retained in the locust's ovaries [22].…”
Section: Introductionmentioning
confidence: 99%